The Corelation Vocabulary Mastery Toward The Result of Reading English - La Ode Hampu; Mildan Arsdan Fidinillah (Scope : Journal of English Language Teaching, 2023)
The purpose of this research is to find out the correlation vocabulary mastery and the result of reading English at eight grade. The research was conducted at junior high school (SMP) Kasih Depok in Depok. The test method used quantitative research, which type of correlation research. The data collection technique used multiple choice objective test totally of items were 80 questions. The questions were consisting 40 items of vocabulary test and 40 items of reading English test. After doing the validity of the test items, then analyzing, and calculating of the test through the use of the Pearson product moment correlation test. It has been obtained T value counting bigger than T table (0,54 > 0,2484) and significant value as 0,000 which is meant less than 0,05(0,000 < 0,05). Therefore, this research has proved the second hypothesis that stated there was positive correlation between vocabulary mastery and the result of reading English at eight grade junior high school (SMP) Kasih Depok.